2023
DOI: 10.3390/nu15092016
|View full text |Cite
|
Sign up to set email alerts
|

Admission Serum Magnesium Levels Is Associated with Short and Long-Term Clinical Outcomes in COVID-19 Patients

Abstract: Background: In the face of the global pandemic that the coronavirus disease 2019 (COVID-19) has created, readily available prognostic markers may be of great use. Objective: To evaluate the association between serum magnesium (sMg) levels on admission and clinical outcomes in hospitalized COVID-19 patients. Methods: We retrospectively analyzed all patients admitted to a single tertiary center with a primary de novo diagnosis of COVID-19. Patients were followed for a mean of 10 ± 7 months. Demographic, clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In our study, the magnesium level was predominantly normal at admission in the majority of patients included in the research, without influencing the survival or the severity of the viral infection. The decrease in serum magnesium levels with negative effects on the body's defense and inflammatory processes has been mentioned in the literature as a high-risk factor, not only for severe prognosis, but also for the development of complications associated with SARS-CoV-2 [56]. Another study described a direct link between hypomagnesemia and symptomatic forms of COVID-19, the persistence of long COVID in elderly patients, prolonged hospitalization, high mortality, as well as a correlation between obese patients with low serum magnesium levels and post-viral death [57].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the magnesium level was predominantly normal at admission in the majority of patients included in the research, without influencing the survival or the severity of the viral infection. The decrease in serum magnesium levels with negative effects on the body's defense and inflammatory processes has been mentioned in the literature as a high-risk factor, not only for severe prognosis, but also for the development of complications associated with SARS-CoV-2 [56]. Another study described a direct link between hypomagnesemia and symptomatic forms of COVID-19, the persistence of long COVID in elderly patients, prolonged hospitalization, high mortality, as well as a correlation between obese patients with low serum magnesium levels and post-viral death [57].…”
Section: Discussionmentioning
confidence: 99%
“…Given the multiple effects of magnesium such as anti-inflammatory and antioxidant effects, it is assumed to play a significant role in COVID-19 development and mortality (47,(73)(74)(75)(76). Results from clinical studies found that the need for mechanical ventilation and mortality rates were higher in hypermagnesemia (magnesium levels > 2.4 mg/dL) and hypomagnesemia (<1.8 mg/dL) patients than in other patients who were hospitalized with COVID-19 (77,78). The COMEPA study found that the low level of serum magnesium was a significant indicator of the onset of long COVID symptoms, length of stay, and in-hospital mortality (79).…”
Section: Magnesium and Pneumoniamentioning
confidence: 99%
“…sMg levels are increased in patients with renal failure secondary to a reduction of magnesium's excretion in the urine [17]. Moreover, it has been shown that these elevations in sMg are not independently associated with poor outcomes but rather serve as a marker for severe renal dysfunction and its implications [18][19][20]. In our cohort, we witnessed an increase in sMg levels in patients with a creatinine clearance (CrCl) of less than 30 mL/min/1.73 m 2 , calculated by the CKD-EPI formula upon admission (Supplementary Figure S1).…”
Section: Study Populationmentioning
confidence: 99%